Juniata, Pottawatomie County - French, Michael (Kansas State University, The Chapman Center for Rural Studies, 2011)
Whether it was the change in beliefs and values, floods and natural damage, or simply the competition with Manhattan, Juniata did not have the means to survive. In life we feel the need to expand and make strides towards progression; I feel that Juniata had its glory as a town united at one point in history, striving for the same goals. However, it was the progression and expansion of surrounding areas that ultimately lead to Juniata’s demise. We as locusts had taken those early traveling and trade resources and now looked for more, across the river to Riley County.
Michael French, “Juniata, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/48.
Keywords: Big Blue River; Ft. Leavenworth-Ft. Riley Military Road; Juniata; Pottawatomie County; Samuel D. Dyer; Tuttle Creek Dam